Survey of potential parasitoids (Hymenoptera) of Drosophila suzukii (Diptera: Drosophilidae) in Buenos Aires province, Argentina - Gallardo, Fabiana Edith (2022)
Drosophila suzukii (Matsumura) is a pest that affects a great variety of fruit crops. The objective of this work was to learn about the diversity of parasitoids (Hymenoptera) that might be associated with SWD in fruit crops located in northeastern Buenos Aires province, Argentina. Species were identified as Euxestophaga argentinensis Gallardo, Ganaspis pelleranoi (Brethes), Leptopilina boulardi (Barbotin, Carton & Kelner-Pillault), Hexacola bonaerensis Reche (Cynipoidea, Figitidae), Trichopria anastrephae (Costa Lima) (Diaprioidea, Diapriidae) and Pachycrepoideus vindemmiae (Rondani) (Chalcidoidea, Pteromalidae). Leptopilina boulardi, E. argentinensis and T. anastrephae were reported for the first time in the Buenos Aires province.